Legal Flexibility in Children Diversion Which Conflict With the Law (ABH) Case Study At Ex Residency of Cirebon Jurisdiction - Muchammad Qomaruddin Qomaruddin; Gunarto Gunarto; Aryani Witasari (Jurnal Daulat Hukum, 2020)
Along with the development of the juvenile justice system practices that have been implemented so far as regulated in Act No. 11 Of 2012 on Child Criminal Justice System (Act of SPPA).The problems of this study are: the flexibility of implementation of diversion in the case of ABH at Ex Residency of Cirebon Juridiction, problems that exist and occur in carrying out the diversion case of ABH in the Ex Residency of Cirebon Jurisdiction, diversion in Case of ABH solutions in the future will come.The method used by researchers is sociological approach juridical law and specification in this study were included descriptive analysis. While the sources and types of data in this study are primary data obtained from the field study interview. And secondary data obtained from the study of literature.Based on the results of research that In accordance with Act No. 11 Of 2012 on Juvenile Justice System, flexibility implementation of new diversion is the stage, which can be done at this stage of the investigation in Children Investigators, or at what stage in the Prosecuting Attorney of the Child, as well as examination by the Child Justice. Hampered that diversion is restricted by a minimum penalty of which may carry out a diversion, even if the victim and the perpetrator (ABH) has  versioned, it turns out if the criminal threat is more than seven (7) years, the diversion that has made News The event can be canceled and further processed to court for trial. Supposedly back in the Draft Bill which is being processed in the House of Representatives of Indonesia, should attempt a diversion in case the child is not constrained by the threat of punishment, because diversion is only mediation enforcement between criminal and victim that in application not sure in agreement.Keywords: Flexibility Law; Diversion; Children; ABH